Inkubasi Ide Kreatif: Pendampingan Penyusunan Proposal Riset Inovatif bagi Kelompok Siswa Peneliti SMP - Sofwan Hadi; Titah Sayekti; Rahmi Faradisya Ekapti; Wilis Werdiningsih (Journal of Community Development and Disaster Management, 2026)
The 21st-century landscape demands that students possess innovation, research, and critical thinking skills as essential competencies in navigating social and technological change. At the junior high school (SMP) level, students have entered a phase of cognitive development that supports the development of scientific, logical, and critical thinking skills. However, this potential is often underdeveloped due to limited space for scientific exploration, teachers' limited methodological competence, and limited coaching time. The Creative Idea Incubation Program offers a solution to facilitate the transformation of student ideas into innovative, measurable research proposals. This article aims to describe the process and outcomes of a mentoring program that developed innovative research proposals for a group of junior high school student researchers and to formulate a replicable mentoring model. The service program was implemented through a two-day intensive workshop involving 32 seventh-grade students, using a service-learning and coaching clinic approach in small-group learning. The Service-Learning stages were carried out through the provision of basic child-friendly research materials, focus group discussions, and presentation and reflection sessions on the prepared proposals. The results showed that students' initial methodological abilities remained heterogeneous, with an average pre-test score of 72.66. Students experience difficulty distinguishing between empirical facts and opinions, formulating hypotheses, and determining data-collection techniques. Mentoring through brainstorming, proposal formulation, and presentation stages has been shown to improve the quality of research proposals, particularly in the formulation of titles, development of backgrounds, and synchronization of research components. This program also contributes to improving students' scientific thinking, creativity, scientific literacy, communication skills, and confidence in conducting innovative research.